Corpo e Velhice: um estudo da qualidade de vida de idosos da Vila Vicentina Júlia Freire em João Pessoa - Pessoa, Stefania Cartaxo (2008)
The aim of this study was to follow the daily routine of elderly individuals residing at the Vila Vicentina Júlia Freire (VVJF) nursing home in João Pessoa, Brazil, observing and analyzing as much as possible, the way in which they live in a group and how they deal, through personal experiences, with their own body image and with that of others. The results were obtained from information considered relevant, according to the perspectives of the residents themselves, contained in narratives of their history and related to their quality of life. Our interest lays in how they coped with changes in their bodies at old age and adapted to the challenges of this new phase. To obtain this information, with significant expressions, we used the Narrative Interview (NI) as a research tool in order to redeem their life experience and develop an understanding of their impressions about the life experience at the current nursing home. We selected, among the housed, ten subjects - actors - to appear as a sample of the group together. The design of our sample had a hybrid model, combining two types: random sample (probability) and an intentional sample (not probability). After recording transcripts and ensuring that all the subjects showed common interests that were relevant to the group, we chose three categories for analysis as follows: a. the elderly as seen by themselves and by others; b. religiosity as a moral factor; c. intimacy and relationships. Our choice was based on the importance of the theme as a multidisciplinary topic in the quality of life of populations. The subjects, chosen as spokespersons for the VVJF, spoke, among other things, about the way in which they viewed the world, their own body and how they experienced the environment and their fellow residents, in an attitude of reflection and criticism that confirms the lucidity of an old age conditioned to an elderly institution. The method allowed us to investigate our subjects from a multidisciplinary point of view. We suggest other studies in assorted areas of the human sciences, having as principle, man at the center of all our scientific questionings. The paradigm that the elder is, necessarily, unhappy in his sheltered has been, in this job, broken through the testimonies collected, establishing multiple perspectives of the analyzed subjects by their respective narrative records. Involving the participation of researchers with major in Administration, Communication and Law, this study filled, in this aspect, the requirements of the multidisciplinarity of the Program of Pos-Graduation in Health Science